Analisis Kecenderungan Perilaku Bullying pada Remaja - Wardani, Jihan Nabilah Putri; Sugara, Gian Sugiana; Rahimsyah, Anandha Putri (Buletin Konseling Inovatif, 2025)
Bullying behavior is an act of violence that is carried out both physically, verbally and socially. Bullying behavior that occurs in adolescents, both perpetrators and victims, has a negative impact in the short and long term. The purpose of this study was to obtain an overview of bullying behavior in class XI students based on gender, and program planning to minimize and reduce bullying behavior. This study uses a quantitative descriptive method to reveal a description of student bullying behavior. The population in this study were students of class XI totaling 408 students. The technique in this study used the saturated sampling method by making members of the population as samples. The results showed that in general the bullying behavior of class XI students both perpetrators and victims were in the low category. Based on the sex of the perpetrators there were significant differences between men and women while for victims there were no significant differences between men and women. Thus the implications of guidance and counseling services based on function are preventive and curative efforts to help prevent and deal with perpetrators and victims of bullying to develop them in a more positive direction.